Estimated Brain Volume Could Affect the Learning Achievement on Medical Student of Sebelas Maret University - Sukamto, Auliansyah Aldisela Januar; ., Muthmainah .; ., Suyatmi . (Nexus Pendidikan Kedokteran dan Kesehatan, 2016)
Introduction: Cranium capacity can reflect the volume of a persons brain. Brain volume is used to estimate a persons intelligence. Intelligence is a persons ability to learn and to understand something new. Intelligence is governed by the left cerebral cortex. Learning achievement is influenced by level of intelligence. The aim of this study was to prove that the correlation between estimated brain volume and learning achievement. Methods: This research was an observational analytic study with cross-sectional design conducted in Medical Faculty of Sebelas Maret University in October, 2015. Samples from this study were 4th year male students of medical faculty. Sixty nine samples were selected by simple random sampling method. Head height, width and length of the participants were measured to determine the brain volume while exams scores were used as learning achievement indicator. Data analysis was performed using Pearson correlation test. Results: The mean of Estimated brain volume and learning achievement measurement were 1614.35, Â± 105.08 cc and 63.9, Â± 4.48 respectively. The majority of samples (85.5%) had an estimated brain volume more than 1500 cc while 14.5% of samples had an estimated brain volume less than 1500 cc. Most of the samples (89.9%) had satisfactory learning achievement while only 10.1% had a good learning achievement. Data analysis using Pearson correlation test showed p = 0.000 and r= 0.555. Conclusion: There was a positive correlation between estimated brain volume and learning achievement on Medical student of Sebelas Maret. This means that the higher estimated volume of brain, the higher the learning achievement. Keywords: estimated brain volume, learning achievement, medical studentÂ